TINJAUAN HUKUM BISNIS ISLAM TERHADAP PENETAPAN HARGA PADA WARUNG INTERNET - Rohmah, Nabilatur; Islami, Trinah Asi (Irtifaq, 2021)
Price fixing carried out by business actors in internet cafe business activities (hereinafter referred to as warnet) is feared to violate the principles of Islamic business law, because the warnet business is a micro business that is highly dependent on electrical energy which has an impact on arbitrary price fixing by business actors to consumers. This research uses a qualitative approach. This type of field research is analyzed inductively by conducting interviews, observation and documentation, then the results of these observations will be obtained by a theory. The results showed that the price fixing made by business actors to consumers after a power cut has two different categories. First, consumers who use this type of member system service do not experience inappropriate pricing. Second, consumers with non-member systems experience inappropriate pricing, where Islamic business law prohibits activities that contain elements of fraud (gharar). Keywords: Islamic Business Law, Price Fixing, Internet Cafes (Warnet)